Comparison of Green Coconut Water with Turmeric and Tamarind Concoction on Reducing Menstrual Pain in Adolescent Girls - Diareski , Viona (International Journal of Medicine And publich Health, 2025)
Background: Adolescence is a transition period or transition from childhood to adulthood which is marked by changes both physically and psychologically. Physical changes are more obvious, the body develops rapidly to reach an adult body shape accompanied by the development of reproductive capacity. One of the characteristics of female puberty is menstruation which is usually experienced by girls aged 10 years, but can also be later, during menstruation the blood that comes out is blood due to the shedding of the uterine wall. Purpose: This study aims to determine the Comparison of Green Coconut Water with Coconut Turmeric Concoction on Reducing Menstrual Pain in Adolescents at SMP Negeri 02 Panyabungan, Mandailing Natal Regency. Method: The type of research used is quasi-experimental research. The population in the study were female adolescents at SMP Negeri 02 Panyabungan. The sampling technique used purposive sampling with a sample size of 40 people. Data collection The research instrument was collecting questionnaire sheets with a Numeric Rating Scale (NRS) pain scale guide to find out respondents in experiencing menstrual pain (dysmenorrhea). Data analysis used the Wilcoxon test with a significance level of p <0.05). Results: The results of the analysis showed that there was an influence with a value of P = 0.000 where P = <0.05. Conclusion: It is recommended that this study can be used in providing nursing care in the reproductive system by providing complementary nursing that recommends green coconut water with turmeric and tamarind concoction as an alternative treatment for menstrual pain. as well as for teenagers who experience dysmenorrhea before using painkillers, it is better to use non-pharmacological treatment, one of which is green coconut water with turmeric and tamarind concoction.